Karakteristik Penderita Sifilis Di Puskesmas Teladan Kecamatan Medan Kota Tahun 2015-2016 - Nurfadillah Arif Harahap; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
ABSTRACT Syphilis still a widespread public health problem in various countries. Syphilis increase the risk of contracting HIV. Research in many countries reports that syphilis infection can increase the risk of HIV transmission by 3-5 times The study aims to describe the characteristics of syphilis patient at Puskesmas Teladan in 2015-2016. This study use secondary data and the case series design followed by bivariate analysis with Chi-Square test. The sample of this study are 210 syphilis patient in Puskesmas Teladan Based on the data which were collected, the highest proportion was obtained at the age of 20-24 years (30%) with the highest age 67 years and the lowest 16 years, male (92.4%), high school (73.3%), unmarried ( 73,3%), people from Medan City (88,6%), risk group at LSL (68,6%), clinical stage at advanced stage (64,3%), visit status referred by NGO (79%) , not syphilis with HIV (76.2%), did not use condom at latest sex (84.3%), sometimes used last week's sex condom (51%), the number of sexual partners per week was more than acouple (81.9%). There is a difference in the proportion between the sex based on the last sex condom use (p = 0.024). There is a recent educational based on the frequency of condom use last week (p = 0.001). There was no difference in the proportion between marital status based on frequency of condom use last 1 week (p = 0,535). Suggested to Puskesmas Teladan to be intensively to educate the risk factors of the suffers, especially avoid unlawful relationships, be faithful to their spouse, and improve cooperation with local stakeholders and NGOs so that the presence of key populations at risk do the examination. To NGOS are more intensive to conduct a search of a WPS-specific key population. Futhermore, the syphilis patient should increase the frequency of condom use and avoid having sex with stangers to reduce the rate of STI transmission. Keywords: Patient with Syphilis, Characteristics.